2020
DOI: 10.1186/s12904-020-00646-6
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of palliative care in a South Asian community: findings from an observational study

Abstract: Background Patients often view “palliative care” (PC) as an approach that is synonymous with end-of-life and death, leading to shock and fear. Differing cultural and social norms and religious affiliations greatly determine perception of PC among diverse populations. Methods This prospective observational study aimed to explore perceptions of PC among South Asian community members at one Canadian site. Patients who identified themsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 28 publications
1
17
0
2
Order By: Relevance
“…As such, to introduce all learners to palliative care, clinical education must be strengthened. Our results support the role of specialist palliative care practitioners [10]. This perspective may lead to the heterogeneity of comprehension of palliative care, affecting the perceptions and use of those patients and families that require it.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…As such, to introduce all learners to palliative care, clinical education must be strengthened. Our results support the role of specialist palliative care practitioners [10]. This perspective may lead to the heterogeneity of comprehension of palliative care, affecting the perceptions and use of those patients and families that require it.…”
Section: Discussionsupporting
confidence: 75%
“…In one report, they found that the national health policy should pay due attention to the PC and that it needs to be integrated into the national nursing education curriculum [9][10]. Some studies have also found that palliative care is about caring for and maintaining comfort for people who die in the last days of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, cultural preferences and structural differences in care provision influence PPC outcomes [ 16 ]. Culture, social norms and religious affiliations determine the perception, acceptance, enrollment and implementation of palliative care services [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding these will allow nurses to provide culturally competent and safe care. 3,14,[27][28][29] Lack of knowledge about ACP and its benefits prevents many AIAHs from planning ACP. Dosani et al 27 found from their observational study of 34 Canadian South Asian adults that a lack of knowledge about palliative care existed among 70% of participants.…”
Section: Acp and Eol Decision Making Among Aiahs: Empirical Evidencementioning
confidence: 99%